Forecasting Energy Prices Using Data Mining Methods - Far, Pejman Bahramian (Eastern Mediterranean University EMU, 2017)
Energy prices have been playing an increasingly significant role in the world economy since all elements involved in this area are considered as a major input for the production. The energy prices as it affect economic variables in the world, is influenced by economic activities of great countries. Indicatively, oil prices which are a major energy index globally are affected by economic activities of great countries, and when such activities are on the decrease, the economy of the industrial countries slips into recession. The energy market is a complex market which does not follow the random walk process. There are many reasons behind the complexity of the energy market such as political situation, etc. Therefore prediction of this type of market is a difficult task. This study aims to investigate, model and forecast the whole US energy market as an important energy market in the world using different machine learning methods. Besides that, the effect of the US inflation on the volatility of the energy market has as well examined. Keywords: Forecasting, Neural Networks, US Energy Market, LPPL Models, Data mining methods

ÖZ: Enerji piyasaları karmaşık bir yapıya sahiptir ve bu piyasalarda oluşan fiyatlar rastsal yürüyüş sürecini takip ederler. Bu karmaşıklığın ardındaki sebepler arasında siyasi gündemin bile dahil olduğu bir çok faktör yer almaktadır. Dolayısıyla enerji piyasalarının öngörülmesi oldukça zordur. Bu çalışmanın amacı Amerikan enerji piyasasını öngörü amacıyla modellemektir. Amerikan enerji piyasasının incelenmesindeki en önemli neden Amerikan ekonomisinin global bir öneme sahip olmasıdır. Bu çalışmada, yukarıda bahsedilenlerin yanı sıra Amerikan enflasyonu ve buna bağlı olarak enerji piyasasının oynaklığı ile olan ilişkisi de incelenmiştir. Enerji ürünleri üretimde ana girdiler olduğundan dünya ekonomisinde gittikçe büyüyen bir role sahiptir. Enerji fiyatları dünya ekonomisindeki bir çok makroekonomik değişkeni etkilemekte büyük ekonomilerin aktiviteleri bu fiyatlar üzerinde etkili olmaktadır. Büyük ekonomilerin aktivitelerindeki yavaşlama ve yükselmeler petrol fiyatalar üzerinde etkili olmakta ve tüm diğer ekonomileri de etkilemektedir. Petrol gibi enerji fiyatlarının öngörülmesi bu nedenle tüm ekonomiler için büyük öneme sahiptir. Anahtar Kelimeler: Öngörü, Yapay Sinir Ağı, Amerika Birleşik Devletleri Enerji Piyasası, LPPL Modeli, Veri Madenciliği
Doctor of Philosophy in Economics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2017. Supervisor: Prof. Dr. Mehmet Balcılar.
Keywords: Economics; Energy Sector-Prices; Forecasting; Neural Networks; US Energy Market; LPPL Models; Data mining methods